Implementation Of Educational Strategic Planning Through The Pancasila Student Profile Strengthening Project - Suharyanto H. Soro; Andi Suhandi; Ferry Timorochmadi; Indra Suryana; Novalia Nurlaela; Premeliani (South Sulawesi Education Development (SSED), 2024)
The purpose of this study is to describe and analyze the implementation of educational strategic planning through the project of strengthening the Pancasila student program at SMPN 43 Bandung.The approach used in this study is a qualitative approach with a descriptive method. Data collection techniques use observation and interviews while analysis techniques use interactive data analysis models which include the data collection stage, data reduction stage, data presentation, and conclusion drawing / verification, the results of the study show that the implementation of educational strategic planning through the Pancasila student profile strengthening project at SMPN 43 Bandung is carried out well and planned. This is evidenced by the steps taken by the Principal in organizing P5 activities. The principal carries out strategic planning with stages of activity, namely planning activities by establishing a P5 Committee of teachers. The core activity of the implementation is by providing material on the theme raised, namely Local Wisdom. And the closing activity by conducting digital-based group evaluations to increase the creative dimension and mutual assistance.